The Impact of knowledge transfer in acquisition processes on ecological innovations in Serbia - Igor Milojević; Marko Savičević; Miloš Dimitrijević (Anali Ekonomskog fakulteta u Subotici, 2024)
Knowledge transfer is a key determinant of the development and implementation of innovations. It has not yet been sufficiently investigated how knowledge transfer can influence the environmental innovations of acquired companies in the Republic of Serbia. This study investigates the role of knowledge transfer in acquired companies in Serbia and examines the impact of knowledge transfer on environmental innovation, i.e. on environmental innovation activities and strategy. The research was conducted based on the answers of 91 respondents, i.e. employees from five companies that were part of the acquisition process in Serbia. Collected primary data were processed in the SPSS program, using statistical analysis such as descriptive statistical analysis, correlational statistical analysis, and regression statistical analysis. Empirical results show that knowledge transfer in acquisition processes has a positive impact on the environmental innovations of acquired companies. The results show that knowledge transfer activities encourage the development and implementation of environmental innovations in those acquired companies. Since there is a lack of studies investigating the environmental orientation of acquired companies, this study contributes to the understanding of how knowledge sharing promotes the development of environmental innovations in acquired companies.